Economic value of east java shrimp exports since 2000-2024 literature review - Moh. Sholeh; Febi Ayu Pramithasari; Sri Rumiyati (Indonesian Institute For Counseling, Education and Therapy, 2026)
Shrimp is one of Indonesia’s leading fishery commodities and contributes significantly to national export earnings in the marine and fisheries sector. East Java Province has become one of the main centers of shrimp production and export due to its extensive aquaculture areas, developed fisheries infrastructure, and access to international export markets. This study uses a Structured Narrative Literature Review (SNLR) approach to analyze the development of the economic value of East Java shrimp exports during 2000–2024. Data were collected from scientific journals, government reports, statistical publications, and fisheries research documents sourced from Google Scholar, Scopus, BPS, and the Ministry of Marine Affairs and Fisheries. The review indicates that shrimp exports from East Java have shown significant growth, particularly after the expansion of whiteleg shrimp cultivation. Export competitiveness is influenced by production capacity, technology adoption, global demand, international quality standards, and trade policies. The study concludes that shrimp exports play a strategic role in regional economic growth and national fisheries development.